2018
DOI: 10.3390/horticulturae4020008
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Physiological Responses of Lettuce Grown under Pre-Dawn or End-Of-Day Sole-Source Light-Quality Treatments

Abstract: The objective of this study was to evaluate growth and physiological responses of 'Cherokee' and 'Waldmann's Green' lettuce (Lactuca sativa) exposed to small changes in light quality and intensity within a 24-h period. Three pre-dawn (PD; 0600 to 0700) and three end-of-day (EOD; 2100 to 2200) treatments were evaluated in the study, each providing 50 ± 2 µmol•m −2 •s −1 of either blue, red, or broadband white light from light-emitting diodes (LEDs). To account for the main daily light integral (DLI), broadband … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
3
9
1
Order By: Relevance
“…Similarly, research has shown that plants grown under monochromatic blue light have longer stems (Liu et al 2011, Nanya et al, 2012, Wollaeger & Runkle, 2014, Kong et al, 2018) and may produce less biomass than those grown under blue‐enriched light supplemented with other wavebands (Hernández et al, 2016; Hernández & Kubota, 2016). However, when used as part of dynamic spectral lighting within a 24‐h period (Chinchilla et al, 2018; Jishi et al, 2016) or during the cropping cycle (H. Spalholz 2019. Thesis, North Carolina State University, Raleigh, NC, USA), monochromatic blue light has been shown to promote lettuce growth by increasing leaf area expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research has shown that plants grown under monochromatic blue light have longer stems (Liu et al 2011, Nanya et al, 2012, Wollaeger & Runkle, 2014, Kong et al, 2018) and may produce less biomass than those grown under blue‐enriched light supplemented with other wavebands (Hernández et al, 2016; Hernández & Kubota, 2016). However, when used as part of dynamic spectral lighting within a 24‐h period (Chinchilla et al, 2018; Jishi et al, 2016) or during the cropping cycle (H. Spalholz 2019. Thesis, North Carolina State University, Raleigh, NC, USA), monochromatic blue light has been shown to promote lettuce growth by increasing leaf area expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The goal has been to use less electrical energy to achieve the same yield and quality. In this special issue, Chinchilla et al [2] evaluated growth and physiological responses of two lettuce cultivars exposed to small changes in light quality and intensity within a 24-h period. They found that 1 h of low intensity end-of-day blue light has the potential to promote lettuce growth by increasing leaf area and shoot fresh mass when the main DLI from sole-source lighting is provided by broadband white LEDs.…”
Section: Manipulating Light In Indoor Vertical Farmingmentioning
confidence: 99%
“…With the advancement of LED technologies, customized light spectra have been made possible. Thus, manipulating light quality (or the spectrum) and light intensity to enhance plant growth and quality has become one of the most popular research fields in recent years, and this special issue has three articles on this subject [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LED lamps have technical advantages over conventional artificial lighting sources such as HPS (High Pressure Sodium Lamp) lamps. A useful feature of LEDs is their inherent ability to provide spectral control with luminous flux customization, which allows plant photoreceptors to perceive light signals that can control morphology and improve product quality (CHINCHILLA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%